Job and the mystery of suffering. - Rohr, Richard (Crossroad, 1997)
"The ancient story of Job that grapples with the question of why there is suffering in the world even for those who lead a good and upright life has challenged, perplexed, and comforted readers for millennia. Here Richard Rohr shares his understanding of the book, both in its historical setting and as a most important message for today. The book speaks most strongly to those whose own world has fallen apart, but in its essence, it is a call to each reader to let go of old certitudes and goals and to place faith and trust radically in God alone." "This book is a spiritual commentary and chapter-by-chapter Scripture study of the many themes that occur throughout the book. In this exploration many questions are raised as much about the reader's own life as Job's, and from this process is promised deeper understanding. In the course of the story, Job witnesses to the reality of pain, but also to gaining a new sense of joy and freedom and restoration of soul."--Jacket.